Male Uro-Rectal Iatrogenic Fistula Treatment in Pelvic Tumours: A National Multi-Institutional Study - E. Martins, Francisco (2017)
Introduction: Urorectal fistulas (URF) are a devastating complication of pelvic tumor treatment and a significant surgical challenge. Despite its increasing incidence associated with an increasing use of different forms of non-surgical treatment of pelvic tumours, urorectal fistula remains rare. Given the improbability of spontaneous closure, surgical correction becomes necessary in almost all cases. Despite the existence of various surgical techniques, rates of failure / recurrence are usually high, particularly in radiation fistulas. In this study the authors describe their experience in the treatment of URF resulting from pelvic tumor treatment. Methods: Between October 2008 and February 2015, 12 male patients were identified with URF treated in our institutions. A review of medical records of patients, including age, symptoms, comorbidity, diagnostic approach, type and fistula etiology, type of surgical reconstruction, follow-up and results was performed. Non-neoplastic / inflammatory fistula patients were excluded from the study. Results: We identified and treated 12 patients. One patient with fistula secondary to anterior resection of the rectum developed lymph node and liver metastases 4 months after the diagnosis of urorectal fistula and was consequently excluded from surgical treatment and study. The mean age of patients was 68 years (53-78). Nine patients developed URF after prostate cancer therapy: Two after low-dose brachytherapy combined with external beam radiation therapy; five after retropubic radical prostatectomy, with adjuvant radiation therapy in one; one after low-dose brachytherapy followed by transurethral resection of prostate; and one after high intensity focal ultrasound and radiation therapy. In two patients, the fistula resulted from surgical treatment of rectal carcinoma, associated with radiation therapy in one of them. In all patients with fecal and urinary diversion was performed by means of colostomy and suprapubic catheterization or urethral catheterization during the waiting period for surgical reconstruction. No spontaneous closure of URF occurred in any patient. Eleven patients underwent surgical reconstruction. Perineal approach was exclusively used in seven patients. In four patients, an abdominoperineal approach was employed. Effective fistula closure was reported in six patients after the first surgical attempt. Two patients required a second surgery, while one patient required three surgical procedures to achieve a successful result. Surgical failure occurred in two patients, which at present do not wish any additional reconstructive attempt. These two patients and one patient, in whom the reconstruction was effective, yet remain with colostomy. The mean follow-up was 25.5 months (3-75). Conclusion: URF are an uncommon but serious complication of treatment of pelvic tumors, usually associated with debilitating morbidity and loss of quality of life. Although a surgical reconstruction can be extremely difficult, in most cases it is possible to have a successful outcome by either a perineal or abdominoperineal approach and the use of interposing tissue when indicated.